Analisis Pengaruh Sikap terhadap Kesehatan dan Label Kepada Kepatuhan Membaca Label Produk Pangan pada Mahasiswa Gizi Provinsi Kepulauan Riau - Herviana Herviana; Haqqelni Nur Rosyidah; Amalina Rizma; Siska Pratiwi; Citra Dewi Anggraini; Made Tantra Wirakesuma (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Badan Pengawas Obat dan Makanan (BPOM) reported that 20.62% of identified food product labels did not meet the provisions. This results in low compliance with reading information labels and nutritional composition among the public. Low compliance with reading information and nutritional labels can occur due to disinterest in information resulting in poor understanding of food product labels. This study aims to analyze the relationship between attitudes towards health and food product labels with compliance with reading food product labels. This research involved 47 students of the undergraduate nutrition study program. Data on attitudes towards health and nutritional labels were obtained using a respondent agreement level form. Data on label reading compliance was obtained from questionnaire. The chi square test is used to analyze the relationship between variables. The research results showed that the majority of respondents (63.8%) had a positive attitude regarding the level of approval of health and food product labels. There is no significant relationship between attitudes towards health and food product labels and compliance with reading nutritional value information labels (p=0.330). Nutrition students are expected to increase their positive attitude towards reading nutritional value information labels through education or practice reading food labels.